APPLYING GEOPHYSICAL METHODS TO STUDY TECTONIC FACTORS IN DAKRONG – HUONG HOA AREA , QUANG TRI PROVINCE - Canh, Nguyễn Văn; Thám, Hoàng Hoa; Tuyến, Đoàn Văn (Hue University Journal of Science: Natural Science, 2017)
Geophysical methods have been known as an efficient tool in investigating distribution and physical properties of rocks based on their differentiation in structure, petrographic composition, physical-mechanical properties and chemical composition. This paper presents the evaluation results of the occurrence of tectonic factors using the resistivity method. The geophysical investigation in the studied area determined the fault and fracture structure developed on geological units whose apparent resistivity varies from more than 1000 Wm (granite) to about 500 Wm (sediments). In each explored sections, one to two fault systems oriented in the directions of Northeast – Southwest and Northwest – Southeast with dips of 35–45° were observed. The results would be a source of significant information for warning possible geological hazards affecting irrigation works, hydropower dams and human activities in the area.